Aerodynamic coefficients and pressure distribution on two circular cylinders with free end immersed in experimentally produced downburst-like outflows. Issue 3 (February 2021) - Romanic, Djordje; Ballestracci, Andrea; Canepa, Federico; Solari, Giovanni; Hangan, Horia
Thunderstorms winds are localized and transient phenomena characterized by three-dimensional non-stationary velocity fields. While numerous studies investigated the wind loading on cantilevered structures under thunderstorm downburst winds, there is a lack of fundamental research on the behavior of simple circular cylinders subjected to downburst-like outflows. This paper investigates the pressure distribution and aerodynamic coefficients of two cylinders with different diameters immersed in three different types of wind: (1) isolated downburst (DB); (2) downburst embedded in an atmospheric boundary layer (ABL) wind (DBABL); and (3) steady ABL wind. The focus of this study is to provide a comparative analysis between aerodynamic coefficients (drag and lift) and surface pressures that result from these three different wind systems. The ABL winds caused a higher drag on the thinner cylinder than the two DB-like outflows. The lift coefficients during the primary vortex passage in the DB-like outflows were negative at the base of the cylinders and approached zero or to slightly positive values close to the cylinders' top. The location of the cylinders in DB-like outflows is the dominant factor for their aerodynamics.